Synthesis and Cyclopolymerzation of N-Aryl Di ‎AllylAmins As Antioxidants for Lubricant's Oil (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this research many new N-aryl substituted di allylAmins were  synthesized [ A1-A2 ] which were Polymerized by free radically mechanism by using Ammonium per sulfate  as an initiator at 700C .The new hindered   amines   as  cyclo  polymers  were  characterized  by FTIR  and  H-NMR Spectroscopies ,Physical   and   chemical properties were measured  using TGA and DSC to   study   the thermal stability  of   prepared  cyclopolymers  . These   prepared  N-aromatic  substituted di allylamins cyclopolymers [ A3 - A4 ]  were  used  as  antioxidants  for  lubricant  oil  .   which   give    high stability   when  comparing  with standard  antioxidant . The oxidation stability of base  oil with (1% ) additive  were  examined according to Institute of Petroleum testing method IP280